Penerapan Budaya K3 Terhadap Kinerja Karyawan Pada Department of Mining PT Semen Baturaja - Yulistia, Eriyana; Sari, Enda Kartika; Risa, Oka (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2023)
The company's goals will be achieved when it has good and qualified human resources. One of indicator that company has a good human resources governance, is when it puts safety and health of its employees as priority. The company through the Occupational Health and Safety (OHS) program, tries to protect its employees in all forms of work activities, as an effort to keep its workers away from accidents or injuries while working. This is also an effort to avoid diseases that occur in the short or long term due to the work that employees do in the company. Department of Mining at PT Semen Baturaja Tbk is one of departement whose activity in working process has high potential risk and danger. This research aims to know the impact of the implementation of OHS culture in the Department of Mining and how deep the implementation of OHS culture effects employee’s performance in working. Multiple Linear Regression Test in the SPSS 18 program is used to examine the data obtained through questionnaires and interviews, the value of the impact of implementing OHS culture on employee performance within the Department of Mining at PT Semen Baturaja will be known. From the analysis conducted, known that the regression coefficient X1 is 0.281, and the regression coefficient X2 is 0.577. From the F Test that conducted, it is obtained that t value is bigger than t table, means that the OHS culture factor has a significant impact on employee performance with a coefficient of determination is 16.5%. Thus, we can conclude that factor of implementing OHS culture has a real impact on employee performance within the Department of Mining at PT Semen Baturaja tbk.